Corporate cash hoarding in a model with liquidity constraints - Falk Mazelis (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
This paper studies the role of uncertainty in the corporate cash hoarding puzzle. The baseline model is a stochastic neoclassical growth model featuring idiosyncratic and uninsurable productivity shocks and a cash-in-advance constraint on new in- vestments on the individual rm level. Individual agents' choices regarding cash holdings are analyzed. After a wealth threshold is reached, the cash-in-advance con- straint ceases to have an e ect on the agent's behavior. The resulting aggregate cash holdings of households increases with uncertainty. Aggregate consumption is also higher, but the added volatility of consumption decreases lifetime utility. Al- lowing rms to borrow and lend available unused cash increases average variables. An exogenous increase in the interest rate at which they intermediate funds leads to increased intermediation activity, corresponding to the lending channel of monetary policy transmission.
Keywords: C63; E21; E41; D81; 330; Cash-in-advance constraint; idiosyncratic risk; corporate cash hoarding; lending channel